2014
DOI: 10.1021/jp500371w
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Novel Cobalt-Free Oxides NdxSr1–xFe0.8Cu0.2O3−δ (0.3 ≤ x ≤ 0.7) as Cathodes of Intermediate Temperature Solid Oxide Fuel Cells

Abstract: Nd x Sr 1−x Fe 0.8 Cu 0.2 O 3−δ (NSFCx, 0.3 ≤ x ≤ 0.7) have been prepared and evaluated as cathodes for intermediate temperature solid oxide fuel cells (IT-SOFC). Their structure, thermal expansion, electric, and electrochemical properties are investigated. The oxides exhibit all cubic structure and show excellent thermal and electrochemical performance stability. The Nd content (x) significantly affects the properties of NSCFx. NSFC0.5 has been found to be the optimum composition with a peak electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 72 publications
0
40
0
Order By: Relevance
“…By fitting the impedance spectra against an equivalent circuit model, one could deconvolute polarisation the ASR (R T ) into two resistances: R 1 resistance at higher frequency (10 21 0 5 Hz) related to charge-transfer process, and R 2 at lower frequency < 10 2 Hz related to non-charge-transfer process including adsorption, diffusion, and dissociation of the oxygen species. [6,42] Figure S7b shows that resistance R 2 is higher than R 1 for all the Li-doped samples, indicating that non-charge-transfer process is the rate-determining step at 600°C. It also revealed that at 600°C the SLFNT50 has the lowest R 2 and 2 nd lowest R 1 among all the Li-doped cathodes.…”
Section: Catalytic Activity For Orrmentioning
confidence: 94%
See 2 more Smart Citations
“…By fitting the impedance spectra against an equivalent circuit model, one could deconvolute polarisation the ASR (R T ) into two resistances: R 1 resistance at higher frequency (10 21 0 5 Hz) related to charge-transfer process, and R 2 at lower frequency < 10 2 Hz related to non-charge-transfer process including adsorption, diffusion, and dissociation of the oxygen species. [6,42] Figure S7b shows that resistance R 2 is higher than R 1 for all the Li-doped samples, indicating that non-charge-transfer process is the rate-determining step at 600°C. It also revealed that at 600°C the SLFNT50 has the lowest R 2 and 2 nd lowest R 1 among all the Li-doped cathodes.…”
Section: Catalytic Activity For Orrmentioning
confidence: 94%
“…[6,42] Figure S7b shows that resistance R 2 is higher than R 1 for all the Li-doped samples, indicating that non-charge-transfer process is the rate-determining step at 600°C. [6,42] Figure S7b shows that resistance R 2 is higher than R 1 for all the Li-doped samples, indicating that non-charge-transfer process is the rate-determining step at 600°C.…”
Section: Catalytic Activity For Orrmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have concentrated on different perovskite-based materials and oxide combinations, that could result in more efficient cathodes in the intermediate temperature range of 500-800°C [3][4][5][6]. In this study we have focused on the Ce 1/3 NbO 3 compound, which is a member of the series Ln 1/3 NbO 3 (Ln = rare earth).…”
Section: Introductionmentioning
confidence: 99%
“…This is because ionic conduction in either electrolyte or electrode is crucial to good performance of a fuel cell [68], and it is strongly desired to look for new ionic (oxide ion and proton) conductors operating at low and intermediate temperatures [9, 10]. The use of ceria-based materials, especially samaria- or gadolinia-doped ceria (SDC or GDC) as electrolyte or as functional layers between electrolyte and electrode, can significantly lower the operation temperature and increase the performance of solid oxide fuel cells due to their higher oxide ion conductivity (0.02 S cm −1 at 700 °C) [11, 12].…”
Section: Introductionmentioning
confidence: 99%